University of Salamanca The Escuelas Mayores Building - NIETO GONZÁLEZ, José Ramón (Historia de la Universidad, 2014)
igmas (see below) was added. At some unknown date, but certainly before 1469 (the year in which people were starting to talk about a square design) another corridor smaller than the present-day one was built. Around 1570, this was reformed with the current corridor on the northern side, under the supervision of Rodrigo Gil de Hontañón, and it became the place where classes were again taught there in 1574-1575. In the second half of the 18th century, todays current chapel and the Salon de Claustros (Senate Hall) were built, and towards the end of the 19th century the cloistered part was completed with another floor built on the eastern corridor and over the northern corridor based on a project by José Secall, who also designed the arch work on the southern corridor. As the culmination of all these constructions and additions, we now have the present edifice, organized around a patio with semicircular arches on the ground floor and five-pointed oge earches on the upper floor, both floors being connected by a magnificent staircase. The disposition of the floors seems to be related to the design of a Roman house, which would in part explain at least for the defenders of this hypothesis the addition of the richly sculpted façade, based on Vitruvian influences.